2019
DOI: 10.1111/ijfs.14476
|View full text |Cite
|
Sign up to set email alerts
|

Texture and colour characteristics, and optimisation of sodium chloride, potassium chloride and glycine of reduced‐sodium frankfurter

Abstract: The three-components mixture design was applied to optimise a ratio of NaCl (0%-65%), KCl (35%-100%) and glycine (0%-20%) in reduced-sodium frankfurters. Fourteen frankfurters were analysed for texture and colour, and consumer (n = 100) acceptability. Results indicated that NaCl levels affected consumer acceptability of reduced-sodium frankfurters. Increasing NaCl generally increased texture hardness. Optimisation of a salt mixture was performed by superimposing contour plots of predicted acceptability scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…In accordance with our results, the low influence of salt replacement was also observed by several authors, who found that partial NaCl did not have or had a minor effect on color parameters [ 6 , 12 , 32 ]. Additionally, the minimal influence of NaCl replacement on color coordinates were classified as “no important difference”, since it may not be discernable by human vision [ 38 ]. Similar results were also reported for lacón, where the authors observed that the partial replacement of NaCl by KCl or two different combinations of KCl, MgCL 2 , and CaCl 2 did not influence color parameters in any manufacturing step, while as the ripening time progressed, a significant decrease in L* and b* and increase in a* values was found [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our results, the low influence of salt replacement was also observed by several authors, who found that partial NaCl did not have or had a minor effect on color parameters [ 6 , 12 , 32 ]. Additionally, the minimal influence of NaCl replacement on color coordinates were classified as “no important difference”, since it may not be discernable by human vision [ 38 ]. Similar results were also reported for lacón, where the authors observed that the partial replacement of NaCl by KCl or two different combinations of KCl, MgCL 2 , and CaCl 2 did not influence color parameters in any manufacturing step, while as the ripening time progressed, a significant decrease in L* and b* and increase in a* values was found [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results of the texture profile analysis (TPA) of reducedsodium Vienna sausages are shown in 2), and were not significantly (p ≥ 0.05) affected by the varying salt mixture A thorough review of the data (Table 2) did not reveal a particular pattern of the effects of the salt mixture and their levels on instrumental texture hardness and firmness as also seen in the literature reporting the effects of salt reduction on textural properties of processed meat products (Wilailux et al, 2020). However, it could be seen that, in several cases, reducing NaCl by addition of KCl and Gly in the salt mixture at different levels significantly (p < 0.05) decreased hardness and firmness ( 2).…”
Section: Effects Of Salt Mixture On Physical Properties Of Laboratory-scale Reduced-sodium Vienna Sausagesmentioning
confidence: 66%
“…Different methods have been successfully applied to reduce sodium in foods, including use of visual cues, particularly colour (Sukkwai et al ., 2018), and odour/flavour (Chokumnoyporn et al ., 2015) and use of foam‐mat salt (Chokumnoyporn et al ., 2016) as well as, the most commonly used method, that is use of salt substitutes (Cerrato‐Rodríguez et al ., 2017; Torrico & Prinyawiwatkul, 2017; Lee & Chin, 2019; Pujols et al ., 2019; Wilailux et al ., 2020; Xiong et al ., 2020). Another approach to salt reduction in foods would be the use of salt enhancer, a compound that magnifies the salty taste at a low level.…”
Section: Introductionmentioning
confidence: 99%